An Early Arctic Small Tool tradition structure from interior Northwestern Alaska - Odess, Dan (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractOver forty years ago, William Irving proposed the Arctic Small Tool tradition (ASTt) to indicate taxonomic unity and historical relatedness among several recently identified mid-Holocene cultures in Alaska (Denbigh Flint complex), Canada (Pre-Dorset), and Greenland (Independence I and Saqqaq). Since then, research in Canada and Greenland has helped refine our understanding of cultural relationships between the eastern members of this tradition, their economies, technologies, and demographic histories. By comparison, research on the Denbigh Flint complex, the Alaskan member of the tradition, has lagged behind. Little fieldwork has been conducted since the mid-1970s, and little attention paid to Denbigh subsistence and settlement systems or to the historical relationship between Denbigh and its neighbors to the east. This paper reports on an Early ASTt site in the western Brooks Range, northwestern Alaska, and discusses its significance within the context of the Early ASTt across the North American Arctic. The structure from the site bears strong similarities to Pre-Dorset, Independence I, and Saqqaq houses from the Canadian Arctic and Greenland, and adds an additional dimension to our understanding of the relationships between the various techno-complexes that compose the Early Arctic Small Tool tradition.